2009
DOI: 10.1007/s11270-009-9986-y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Changes and Heavy Metal Partitioning in an Oxisol Cultivated with Maize (Zea mays, L.) after 5 Years Disposal of a Domestic and an Industrial Sewage Sludge

Abstract: The need for solutions to minimize the negative environmental impacts of anthropogenic activities Fhas increased. Sewage sludge is composed of predominantly organic matter and can be used to improve soil characteristics, such as fertility. Therefore, its application in agriculture is an adequate alternative for its final disposal. However, there is a lack of information on its long-term effects on soil changes in tropical areas. Thus, the objectives of this study were to determine (i) the effect of sewage slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…From 2007 to 2014, many studies have reported the heavy metals risk associated with the amendment of sludge to soil (Alcantara et al, 2009;Antoniadis et al, 2007;Brazauskiene et al, 2008;Carbonell et al, 2009;Lag-Brotons et al, 2014;Oladeji et al, 2012;Yeganeh et al, 2010). However, there is certain boundedness on the conclusions obtained by these researchers mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…From 2007 to 2014, many studies have reported the heavy metals risk associated with the amendment of sludge to soil (Alcantara et al, 2009;Antoniadis et al, 2007;Brazauskiene et al, 2008;Carbonell et al, 2009;Lag-Brotons et al, 2014;Oladeji et al, 2012;Yeganeh et al, 2010). However, there is certain boundedness on the conclusions obtained by these researchers mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…15 Sewage sludge used as fertilizers might contaminate crops, soils, superficial and underground waters with nitrates, heavy metals, pathogens, various classes of organic compounds and persistent organic compounds. 14,16,17 In Brazil, the use of SS in agriculture is regulated through the directive CONAMA357/2005. 18 There is little information in the literature about PAH uptake by plants from SS-treated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Soil samples were obtained from a field experimental area of Embrapa Meio Ambiente (Embrapa Environment), where a long-term experiment was carried out with corn plants grown in soils amended with SS for six consecutive years. 11,14,26 Experimental Field experiments were carried out in a clay texture distroferric red oxisol (sand loam rhodic oxisol, typic Nine experimental plots of 10 × 20 m cultivated with corn plants were used. The experiment was arranged in randomized complete blocks with three replications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations